Being Creative Early on is the Main Capital for Entrepreneurship - Muhammad Solahuddin (Jurnal PKM Manajemen Bisnis, 2021)
Being a trader is not easy, let alone being an entrepreneur, is very difficult. Indeed, the ability to trade or do business is one of the life skills that must be possessed. The reason is, business competence is one of two life skills, therefore each of us must learn it. This community service activity is carried out as one of the contributions of the academic world to people's lives. In principle, this activity is one of the real forms of theory learned during college. The method used in service activities is education and discussion. In the education section, an explanation is given about how to be a creative and innovative person, so that they can become a reliable entrepreneur or trader. Meanwhile, at the discussion stage, experiences from business actors were presented. The end of this activity is to motivate the participants to be able to explore their interests and talents, as well as seek insight into entrepreneurship by looking at business activities that exist in the Community.